2009
DOI: 10.3892/or_00000445
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic inhibitory effect of gemcitabine and angiotensin type-1 receptor blocker, losartan, on murine pancreatic tumor growth via anti-angiogenic activities

Abstract: Abstract. Pancreatic cancer is one of the leading causes of cancer death, and represents a challenging chemotherapeutic problem. The crucial role of angiogenesis in tumor growth has been widely recognized, and several reports have revealed that the combination treatment of the conventional chemotherapeutic drugs and anti-angiogenic agents exerted synergistic anti-cancerous effects. It has been reported that the clinically used angiotensin type-1 receptor blocker (ARB) exerted potent anti-angiogenic activity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…A retrospective cohort led by Y Nakai et al reported that the ACEIs/ARBs in combination with gemcitabine might improve clinical outcomes in patients with advanced pancreatic cancer [ 39 ]. Besides, Ryuichi Noguchi et al found that losartan could also sensitize PDAC to gemcitabine regimen via anti-angiogenic activities [ 40 ]. In pancreatic cancer, cancer cell-derived cytokines activate pancreatic stellate cells (PSCs) forming the CAF phenotype and contributing to extensive pancreatic desmoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort led by Y Nakai et al reported that the ACEIs/ARBs in combination with gemcitabine might improve clinical outcomes in patients with advanced pancreatic cancer [ 39 ]. Besides, Ryuichi Noguchi et al found that losartan could also sensitize PDAC to gemcitabine regimen via anti-angiogenic activities [ 40 ]. In pancreatic cancer, cancer cell-derived cytokines activate pancreatic stellate cells (PSCs) forming the CAF phenotype and contributing to extensive pancreatic desmoplasia.…”
Section: Discussionmentioning
confidence: 99%